THE FALL OF CINEMA ATTENDANCE IN THE ERA OF "STAGNATION". CAUSES AND CONSEQUENCES - M. Kosinova (Вестник университета, 2016)
The article discusses the process of the fall of cinema attendance that took place in Soviet cinema in the 1970's - early 1980-ies. The author examines the causes of this negative tendency and the measures that took the leaders of the Soviet cinematography and the filmmakers to eliminate this problem. The article contains the questions of cinema sociology, movie rental, repertoire policy.